REALIZATION THE CONCEPT OF “EDUCATION” IN MODERN LINGUISTICS - Xilola Mahmudjonova Avazbek qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The goal of this work is to demonstrate the necessity of moving beyond the concept of education's nominal definition and to support the existence of distinctive characteristics of the term's true definition in character and sense, which must always be taken into consideration It concerns developing standards for what constitutes "education" and the significance of learning in the development of educational fields. Building educational fields over cultural domains is achievable thanks to knowledge of education, which transforms information into knowledge and knowledge into education. And to do this, one must build an educational relationship in which shared activity serves as the main working tool while competently carrying out teaching functions.